2013
DOI: 10.1039/c3nr34222k
|View full text |Cite
|
Sign up to set email alerts
|

High performance amorphous ZnMgO/carbon nanotube composite thin-film transistors with a tunable threshold voltage

Abstract: Here we report the fabrication and characterization of high mobility amorphous ZnMgO/single-walled carbon nanotube composite thin film transistors (TFTs) with a tunable threshold voltage. By controlling the ratio of MgO, ZnO and carbon nanotubes, high performance composite TFTs can be obtained with a field-effect mobility of up to 135 cm(2) V(-1) s(-1), a low threshold voltage of 1 V and a subthreshold swing as small as 200 mV per decade, making it a promising new solution-processed material for high performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…The mobility obtained in this work is also compared with the mobilities reported by other works on sol-gel oxide TFTs in Table S3 in supporting information 5 6 9 10 11 16 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 . There are several reports on oxide TFT using various approaches to improve the mobility as high as 140 cm 2 /Vs 37 .…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The mobility obtained in this work is also compared with the mobilities reported by other works on sol-gel oxide TFTs in Table S3 in supporting information 5 6 9 10 11 16 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 . There are several reports on oxide TFT using various approaches to improve the mobility as high as 140 cm 2 /Vs 37 .…”
Section: Resultsmentioning
confidence: 68%
“…There are several reports on oxide TFT using various approaches to improve the mobility as high as 140 cm 2 /Vs 37 . These approaches include the plasma treatment 26 27 , the incorporation of conductive nanotube/nanowire 30 36 37 , and the introduction of new precursor and new compound 16 34 35 38 , etc. Without using these treatments, the mobility reported on sol-gel IGZO TFT is typically 0.0007-0.8 cm 2 /Vs with 300 °C annealing temperature 11 25 26 , 0.02-1.56 cm 2 /Vs with 450 °C annealing temperature 29 30 31 32 33 , and 6.415 cm 2 /Vs with 600 °C annealing temperature 25 .…”
Section: Resultsmentioning
confidence: 99%
“…By using density gradient ultracentrifugation method well-known for sorting mixtures of SWCNTs, solutionprocessed SWCNT TFTs possess a large on/off current ratio (~10 5 ) with a high field-effect mobility (~30 cm 2 /V s) in the linear region [13,14]. However, large positive threshold voltage (V T ) resulting in a depletion mode of operation, normally observed in solutionprocessed SWCNT TFTs, can be still a big challenge to realize high performance CNT-based nanoelectronics [15,16]. Furthermore, it is a critical factor to develop molecular-scaled devices requiring low power consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The research on insulating layers is a heated topic in the field of thin film transistors (TFTs), since gate dielectric materials have great effects on the device as a key component of TFT [ 1 , 2 , 3 , 4 , 5 ], and more concern about better performance of the gate dielectric materials has been attracted nowadays. Dielectric properties of materials determine the ability to store charges and influence the leakage current between gate and active layer directly.…”
Section: Introductionmentioning
confidence: 99%
“…The research results from Ku and Chen et al [ 33 , 34 ] showed that Mg 2+ can suppress oxygen vacancy defects because of its high oxygen affinity. This is an effective way to solve the high leakage current caused by defects [ 5 , 23 , 35 ]. Y 3+ is a good carrier inhibitor due to the low electronegativity and small standard electrode potential of yttrium, as shown in the studies done in 2012 and 2014 [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%